Earnings Manipulation in Failing Firms - Rosner, Rebecca L. (Contemporary Accounting Research, 2003)
Abstract Prior literature and anecdotal evidence, most recently provided by allegations relative to Enron, Global Crossing, and WorldCom, suggest that failing firms (defined here as prebankruptcy firms) may be motivated to engage in fraudulent financial reporting to conceal their distress. I examine two research questions: (1) Are failing firms' prebankruptcy financial statements more likely to exhibit signs of material income increasing earnings manipulation than those of nonfailing firms? (2) Do auditors detect the overstatements in firms that they perceive to be failing? I predict and find that as (ex post) bankrupt firms that do not (ex ante) appear to be distressed approach bankruptcy, their financial statements reflect significantly greater material income‐increasing accrual magnitudes in nongoing‐concern years than do control firms. The accrual behavior of these firms resembles that of bankrupt firms that the Securities and Exchange Commission (SEC) has sanctioned for fraud. Like sanctioned firms, the nonstressed bankrupt firms display significantly greater (material) increases in receivables; inventory; property, plant, and equipment; sales; net working capital, current, and discretionary accruals in prebankruptcy nongoing‐concern years than do control firms. They also display significantly more negative changes in cash flows from operations and net cash and a greater disparity between accrual‐based net income and operating cash flows than do control firms, consistent with Lee, Ingram, and Howard 1999. Finally, I predict and find that these firms' going‐concern years reflect evidence consistent with auditor‐prompted reversal of previous overstatements. These results are based on parametric and nonparametric tests for various subsample combinations drawn from a sample of 293 bankrupt firms representing approximately 2,500 observations.